Development of Teaching Materials for Ilm al-Ma‘ani Based on Literary Appreciation at the University Level in Indonesia: تطوير مواد تعليم علم المعاني على أساس التذوق الأدبي للمرحلة الجامعية يإندونيسيا - Edi Kurniawan Farid; Nurul Murtadho; Bakri Muhammad Bakhiet (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to (1) develop instructional materials for ʿIlm al-Maʿani grounded in literary appreciation and (2) examine the feasibility of these materials. Employing a Research and Development (R&D) approach based on the Borg and Gall model, the study was conducted in three stages: preliminary study and needs analysis, development, and evaluation. The results indicate that the developed ʿIlm al-Maʿani materials, which integrate literary texts, text comprehension, appreciation of aesthetic values, and mastery of ʿIlm al-Maʿani concepts, are comprehensive. The materials include clearly defined learning objectives, content, instructional methods, and evaluation tools. Expert and teacher validation yielded a score of 93.4, placing the materials in the “highly feasible” category. Student evaluations rated the materials as “excellent,” with an average score of 90.8. These findings suggest that incorporating literary appreciation into balaghah instruction enhances both feasibility and learner engagement. The significance of this research lies in linking balaghah with literature through the integration of literary texts in the developed materials. Furthermore, the study contributes to producing ʿIlm al-Maʿani instructional materials that emphasize literary appreciation and are ready for direct implementation at the university level.